Garda Perdamaian Dunia: Peranan Kontingen Garuda II Sebagai Pasukan Perdamaian di Republik Kongo (1960-1961) - wisnu arsa tanjung; Murdiyah Winarti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2020)
The main problem discussed in this article is how the efforts carried out by the Garuda II contingent in the Republic of the Congo. The purpose of this study is to examine more closely the involvement of the Garuda II contingent in the Republic of the Congo both regarding preparations for carrying out tasks in the Republic of the Congo and the activities carried out by the Garuda II contingent while in the Republic of the Congo in 1960 to 1961. The research method used is a historical method that includes several steps, namely heuristics (collecting sources) both oral and written sources, source criticism, interpretation, and historiography. To deepen the analysis, the authors use the approach of the science of sociology, the science of international relations. The research technique used is the study of literature. Based on the results of the study, the Indonesian Government participated in sending peacekeepers to the Republic of Congo under the auspices of the United Nations in 1960 is one implementation of the political spirit of anti-colonialism and imperialism by implementing a free and active foreign policy. Activities were undertaken by the Garuda II Contingent Forces namely overcoming and mediating the rebellions that occurred in the Republic of Congo such as overcoming the battle of sending Garuda Contingent II to Boende and Coquihalville City, the battle of Kamina, the explosion of mines in Kamina and overcoming the movement of separatism in Katanga Province. Besides, conducting patrols to the Bikoro area, Igende. From these activities, the Garuda II Contingent Forces succeeded in carrying out their duties to have a very positive impact on the troops. Indonesian contingent so that the following year the Indonesian Government sent the Garuda Contingent back in 1962.